New perspectives on Microsoft Visual Basic 5.0 for Windows introductory - Ekedahl, Michael V. (New perspectives series, 1998)
Microsoft VisualBasic 5.0 is the subject of this work. It provides an introduction to this programming language. Tutorials cover getting started, understanding code and variables, and objects and the events they generate.